SASTRA HIJAU PENYELAMAT BUMI - Risa Yanuarti Sholihah, Utia Putri Utami, Venty Saskia Rohmalita (Universitas Islam Malang, 2021)
Natural conditions are increasingly poor. The destruction of nature is happening everywhere. The water is no longer clean, the air becomes dirty, and the environment is no longer green. Unfortunately, human awareness of nature preservation is low. In the name of modernization and development, humans carry out large-scale actions regardless of their impact on the environment. This habit is considered natural. Now, nature which is the carrying capacity for human survival has become a killing force. The method used is meta nalasis. Two different views, namely anthropocentrism and ecocentrism are presented in the meaning of nature. Green literature is here to campaign for saving the earth. Green literature does not just contain beauty, but brings people to reflect on the majesty and frustration of humans towards the environment. The movement to save the environment through green literature is increasingly echoed. The idea raised in this article is in the form of a green literary literacy movement. Through the green literary literacy movement, the call to love and care for nature is echoed. A noble act of response to the increasingly miserable conditions of nature.